Rare, endangered and protected plant species of synanthropic flora of the Kampinos National Park (Central Poland) - Kirpluk, Izabella; Bomanowska, Anna (Biodiversity: Research and Conservation, 2008)
The aim of this paper is to present the rare, endangered and protected plant taxons growing in the synanthropic habitats of the Kampinos National Park. The research was conducted on agricultural fields (still maintained) and in ruderal habitats in over a dozen abandoned villages in the Kampinos Forest. Among species considered to be endangered are: Agrostemma githago, Asperugo procumbens, Atriplex rosea, Camelina microcarpa, Centunculus minimus, Filago arvensis, Fumaria officinalis, Gagea pratensis, Holosteum umbellatum, Myosurus minimus, Pulicaria vulgaris and Radiola linoides. To the category of rare plant species belong: Anthemis ruthenica, Arabis glabra, Arnoseris minima, Chenopodium ficifolium, Ch. pedunculare and Euphorbia peplus. Species protected by law, found during the study, include: Epipactis helleborine, Jovibarba sobolifera and Helichrysum arenarium. According to our observations some of the segetal plant species, for example Filago arvensis, Centaurea cyanus and Papaver rhoeas, have tendencies to habitat change. These plant species move from agricultural fields to ruderal habitats. In the Kampinos Forest’s synanthropic habitats the species from seminatural non-forest habitats such as Sedum sexangulare, Eryngium planum, Cerastium semidecandrum, find their place.